Extraction of fixed oil and thymoquinone rich fractions (TQRF) - Ismail, Maznah; AI-Naqeeb, Ghanya; Chan, Kim Wei; Adnan, Raja Nurzatul Efa (2014)
The present invention reported that SFE is suitable for Nigella sativa seeds oil extraction and fractionation. TORF that were produced through SFE extractions (600 bars/40?C) and fractionations (100-200 bars/40-60?C) possessed high level of TO and antioxidant activity. SFE fractionation efficiently concentrates the TO content and antioxidant activity of Nigella sativa seeds oil in short time and low cost manners without using any hazardous organic solvents.